Maxillary Alveolar Ridge Expansion with Split-Crest Technique Compared with Lateral Ridge Augmentation with Autogenous Bone Block Graft: a Systematic Review - Thomas Starch-Jensen; Jonas Peter Becktor (eJournal of Oral Maxillofacial Research)
Objectives: The objective of the present systematic review was to test the hypothesis of no difference in implant treatment outcome after maxillary alveolar ridge expansion with split-crest technique compared with lateral ridge augmentation with autogenous bone block graft.